POTENSI BAKTERI ASAM LAKTAT SEBAGAI BIOKOAGULAN DAN KITOSAN SEBAGAI PENGAWET ALAMI DALAM PROSES PEMBUATAN TAHU BEKATUL - Lusiana Candra Dewi; Hidayah Muji Astuti; Mutiara Sari; Rusmini Rusmini (Universitas Sebelas Maret, 2014)
Abstract- Tofu rice bran is one form of diversification tofu when not socialized . Tofu as a source of vegetable protein so the impact of tofu as a food product that can not be stored longer that required the use of a natural preservative solution that is safe and without any residue . Deacetylation of chitin chitosan as a result polycationic nature so as to reduce the rate of growth of pathogenic bacteria . Potential of Lactic Acid Bacteria ( LAB ) as a producer of lactic acid is expected to act as a natural biocoagulant . The purpose of the study was to determine the potential of chitosan as a natural preservative and potential of LAB as natural biocoagulant in the manufacturing process tofu rice bran. The research method are three stages: the first stage includes : BAL isolation and cultivation of industrial products fementasi yoghurt ; the second stage includes the study of the amount of inoculum BAL ( 5 % , 10 % , 20 % ) as biocoagulant ; study the concentration of chitosan ( 0.5 % , 1 % , 2 % ) as a natural preservative and the mixtures of rice bran and soy whey ( ratio 1 : 1 , 2 : 1 , 3 : 2 ) in the process of making tofu rice bran ; The third stage involves analysis of product tofu rice bran for fat content , protein content , fiber content and microbial contamination include MPN Coliform , Salmonella and organoleptic Hedonic test the level of preference ( color , smell , consistency , flavor ) by panelists . The results showed that tofu rice bran with 10 % inoculum biocoagulant , concentration of chitosan 2 % as a preservative and ratio of rice bran and whey ( 2:1 ) showed the most excellent organoleptic . Keywords : Lactic Acid Bacteria ( LAB ) , biocoagulan t, chitosan , natural preservative , tofu rice bran